2019
DOI: 10.3892/etm.2019.7809
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 gene in the regulation of periodontitis and its molecular mechanism

Abstract: Regulatory effect of Toll-like receptor 4 (TLR4) gene on periodontitis in mice was investigated to explore its possible mechanism. Thirty C57/BL6 mice were randomly divided into the blank control group (N group, n=10), the periodontitis group (P group, n=10) and the periodontitis + TAK-242 group (PT group, n=10). The mice in P and PT group were ligatured with silk threads dipped with porphyromonas gingivalis (P. gingivalis) in the logarithmic phase to induce experimental periodontitis, and TAK-242 was intraper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
0
14
0
2
Order By: Relevance
“…TLR4 has been proved to be crucial in periodontitis pathogenesis ( Renn et al, 2018 ). A previous study indicated that TLR4 can remarkably increase inflammatory responses in vivo , and inhibiting TLR4 can significantly improve the symptoms of periodontitis in mice ( Qi et al, 2019 ). Therefore, we conclude that circMAP3K11/miR-511-3p/TLR4 regulatory axis affects the functions of PDLSCs and increases the inflammatory responses in the development of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 has been proved to be crucial in periodontitis pathogenesis ( Renn et al, 2018 ). A previous study indicated that TLR4 can remarkably increase inflammatory responses in vivo , and inhibiting TLR4 can significantly improve the symptoms of periodontitis in mice ( Qi et al, 2019 ). Therefore, we conclude that circMAP3K11/miR-511-3p/TLR4 regulatory axis affects the functions of PDLSCs and increases the inflammatory responses in the development of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that TLR4 is critical for the activation of NF-κB and the subsequent production of pro-inflammatory cytokines that are implicated in a variety of diseases (19)(20)(21). As a transcription factor, NF-κB serves vital roles in numerous processes, including inflammation, immunity and cell proliferation (22).…”
Section: Discussionmentioning
confidence: 99%
“…Th1 cells differentiate from naïve T cells under the influence of the inductive signals IL-12 and IFN-α. In PD, an upregulation of GATA-3 signaling was noted [ 147 ]. GATA-3 was previously reported to suppress STAT4 signaling and thereby limit the differentiation capacity of Th1 cells and in the meantime enhance that of Th2 cells [ 148 ].…”
Section: Oscc Immune Permissive Environment Induced By Periodontal Diseasementioning
confidence: 99%